SORTING OUT THE LIABILITY DEBATE - COHN,ROBERT; FRIDAY,CAROLYN; MARINI, RICHARD; POWELL,WILLIAM (Tufts Archival Research Center, 2007)
Article discussing the liability of employers and claims that environmental tobacco smoke (ETS) caused illness as a result of on-the-job activities in Sweden. Forecasts possible claims in the United States. Discusses the practice of refusing to hire smokers.